Research on Influencing Factors of Knowledge Hiding Behavior in Socialized Q&A Communities: Taking Zhihu as an Example. (27th September 2022) - Li, Wen-Zhu; Chen, Jiang-Fei; Feng, Xin; Yan, Qiang
Abstract : With the normalization of epidemic prevention and control, the expression of the public's demand for health information on online platforms continues to increase, while knowledge hiding behavior has seriously hindered the communication and dissemination of epidemic prevention knowledge and has a negative impact on public communication and access to health information in the socialized Q&A communities. Therefore, further stimulating diving users' activity and reducing their knowledge hiding behavior have become the key to the sustainable development of epidemic prevention and control and communities. Based on the social cognition theory, from the perspective of individual cognition and external environment, this study constructs a theoretical model of the influencing factors of users' knowledge hiding behavior in the socialized Q&A communities in the post-epidemic era and puts forward relevant assumptions. 151 effective questionnaires are collected and an empirical analysis is carried out by using the structural equation model. The results show that outcome expectation, community atmosphere, and requesting negatively affect knowledge hiding behavior; self-efficacy, outcome expectation, and community atmosphere negatively affect the three different types of knowledge hiding behavior, which are evasive hiding, playing dumb, and rationalized hiding; community atmosphere positively affects outcome expectation, which plays a significant intermediary effect between community atmosphere and knowledge hiding behavior. The research content and relevant conclusions of this study deepen and expand the connotation and extension of knowledge hiding behavior in the negative performance of Q&A communities. From the perspective of practical application, it can also effectively reduce knowledge hiding behavior, grasp the development direction of public health needs, and strengthen the dissemination of epidemic prevention and control knowledge.